Emotional intelligence and job performance: a study with MSCEIT, BPR-5 and 16PF - Cobêro, Cláudia; Primi, Ricardo; Muniz, Monalisa (Paidéia (Ribeirão Preto), 2006)
This research had as objective to investigate the validity of a emotional intelligence measure correlating it with measures of intelligence, personality, and job performance. The participants were 119 subjects, aged 17 to 64 years old, of bothe sex that work in cities industries from the state of São Paulo. The instruments used: the Mayer-Salovey-Caruso-Emotional Intelligence Test (MSCEIT), protuguese version, the Sixteen Personality Factors Questionnaire (16PF), the Battery of Reasoning (BPR-5) a performance evaluation made by two persons (supervisor and a colegue). The results show low correlations between emotional intelligence and personality. Also that the branch managing emotions is correlated with job performance and presents validy with the intelligence. In sum it was concluded that emotional intelligence constitutes a differentiated type of intelligence useful for psychological assessment in the context of industrial and organizational psychology.